“Brazil has its eye on you”: sexual panic and the threat of sex tourism in Rio de Janeiro during the FIFA World Cup, 2014 - Thaddeus Blanchette; Ana Paula da Silva (Brasiliana: Journal for Brazilian Studies, 2016)
The present article draws upon ethnographic research undertaken in the principal sexual commercial zones of the city of Rio de Janeiro and in the institutions and agencies responsible for combating sexual exploitation in Rio during the 2012-2014 period, as well as the analysis of media stories, to explain how and why carioca authorities have not been able to discover and repress the sex crimes they claim exist on a massive scale. We seek to show what effects the moral panic over child sexual exploitation during the 2015 World Cup has had in transforming security in Rio de Janeiro.